Haloperidol and aripiprazole impact on the BDNF and glucocorticoid receptor levels in the rat hippocampus and prefrontal cortex: effect of the chronic mild stress - Osacka, Jana; Koprdova, Romana; Tillinger, Andrej; Pirnik, Zdenko; Kiss, Alexander (Endocrine regulations, 2021)
Objective. Changes in the brain derived neurotrophic factor (BDNF) and glucocorticoid receptor (GR) expression in the prefrontal cortex (PFC) and hippocampus (HIP) are associated with psychiatric diseases and stress response. Chronic mild stress (CMS) may alter BDNF as well as GR levels in both the PFC and the HIP. The aim of the present study was to find out whether chronic treatment with a typical antipsychotic haloperidol (HAL) and an atypical antipsychotic aripiprazole (ARI) may modify the CMS effect on the BDNF and GR expression in the above-mentioned structures. Methods. The rats were exposed to CMS for 3 weeks and from the 7th day of CMS injected with vehicle (VEH), HAL (1 mg/kg) or ARI (10 mg/kg) for 4 weeks. BDNF and GR mRNA levels were established in the PFC and the HIP by Real Time PCR, whereas, PFC and HIP samples were obtained by punching them from 500 μm thick frozen sections. C-Fos immunoreactivity was analyzed in the PFC and the HIP on 30 μm thick paraformaldehyde fixed sections. Weight gain and corticosterone (CORT) levels were also measured. Results. The CMS and HAL suppressed the BDNF and GR mRNA levels in the PFC. In the HIP, CMS elevated BDNF mRNA levels that were suppressed by HAL and ARI treatments. The CMS decreased the c-Fos immunoreactivity in the PFC in both HAL- and ARI-treated animals. In the HIP, HAL increased the c-Fos immunoreactivity that was again diminished in animals exposed to CMS. Stressed animals gained markedly less weight until the 7th day of CMS, however, later their weight gain did not differ from the unstressed ones or was even higher in CMS+HAL group. Un-stressed HAL and ARI animals gained less weight than the VEH ones. Neither CMS nor HAL/ARI affected the plasma CORT levels. Conclusion. The present data indicate that HAL and ARI in the doses 1 mg/kg or 10 mg/kg, respectively, does not modify the effect of the CMS preconditioning on the BDNF and GR mRNA levels in the PFC or the HIP. However, HAL seems to modify the CMS effect on the HIP activation.
Keywords: Hippocampus; krysa rodu Rattus; Rats; antipsychotika; aripiprazol; mozkový neurotrofický faktor; hipokampus; zvířata; receptory glukokortikoidů; Aripiprazole; Brain-Derived Neurotrophic Factor; prefrontální mozková kůra; Receptors, Glucocorticoid; haloperidol; Haloperidol; Prefrontal Cortex; Antipsychotic Agents; Animals